The application of the braille version of nawawi's 40 hadith among people with visual impairment - Mohd Noor A.Y.; Mohd Kashim M.I.A.; Ab Rahman Z.; Mohd Othman F.; Mohd Mokhtar A. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus